Impact of COVID-19 stress on the psychological health of sexual & gender minority individuals: A systematic review - Datta, Sumona; Mukherjee, Tilottama (Frontiers in Global Women's Health, 2023)
The differential effect of the Covid-19 pandemic on the mental health of the population around the globe is well documented. Social isolation, loss of job, financial crisis, and fear of infection due to the pandemic have widely affected people across countries, and the sexual and gender minority (SGM) group is no exception. However, the additional stressors like stigma, discrimination, rejection, non-acceptance, and violence associated with diverse sexual orientation complicated the situation for the SGM group in the context of the Covid-19 pandemic. The present study conducted a systematic review of research (n=16) investigating the impact of Covid-19 stress on the psychological health of SGM individuals. The review had two objectives: a) to explore the effect of the stress associated with the pandemic on the psychological health of the SGM individuals; and b) to identify potential stressors associated with the Covid-19 pandemic affecting the mental health of the SGM individuals. The review provided new insights into the mental health issues of the SGM individual in the Covid-19 context. The findings have important implications for psychologists and social workers working with this population and policymakers around the globe.